2018
DOI: 10.1016/j.scitotenv.2017.08.276
|View full text |Cite
|
Sign up to set email alerts
|

EMD-regression for modelling multi-scale relationships, and application to weather-related cardiovascular mortality

Abstract: In a number of environmental studies, relationships between nat4ural processes are often assessed through regression analyses, using time series data. Such data are often multi-scale and non-stationary, leading to a poor accuracy of the resulting regression models and therefore to results with moderate reliability. To deal with this issue, the present paper introduces the EMD-regression methodology consisting in applying the empirical mode decomposition (EMD) algorithm on data series and then using the resulti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 69 publications
(82 reference statements)
0
12
0
Order By: Relevance
“…This negative association between temperature and CVD health has been found in other parts of the world, such as Lille in France [ 44 ] or Honk Kong in China [ 45 ]. Specifically, in Montreal, it has been shown that found that cold weather induces more CVD deaths than hot weather [ 46 , 47 ]. Furthermore, absolute values for the coefficients increased in higher quantiles, which indicates stronger relationships in the peaks.…”
Section: Discussionmentioning
confidence: 99%
“…This negative association between temperature and CVD health has been found in other parts of the world, such as Lille in France [ 44 ] or Honk Kong in China [ 45 ]. Specifically, in Montreal, it has been shown that found that cold weather induces more CVD deaths than hot weather [ 46 , 47 ]. Furthermore, absolute values for the coefficients increased in higher quantiles, which indicates stronger relationships in the peaks.…”
Section: Discussionmentioning
confidence: 99%
“…The aggregation could also be helpful in studies dealing with exposures with less acute effects such as humidity on cardiovascular mortality during spring (e.g. Masselot et al, 2018). On the other hand, there is a loss of information in the aggregation process, especially concerning health peaks.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been shown that temperature affects cardiovascular mortality and morbidity (e.g. Bayentin et al, 2010;Bustinza et al, 2013;Masselot et al, 2018). Therefore, in order to efficiently organize private and public health service and mitigate the effect of temperature on cardiovascular diseases, it is important to understand every aspect of the relationship.…”
Section: Application and Comparisonmentioning
confidence: 99%
“…This extension allows each IMF to represent a narrow frequency band, aiding both interpretation and the subsequent regression model. In this study, two white noise variables are added with a standard deviation equal to 20% of the standard deviation of temperature time series, as recommended in previous studies [ 34 ].…”
Section: Methodsmentioning
confidence: 99%